Management of Glenoid Bone Loss in Primary Reverse Total Shoulder Arthroplasty - Erick Marigi, MD; Kristin E. Yu, MD; Amanda Vasquez-Loret, MS; Michael D. Baird, MD; Christopher M. Hart, MD; John W. Sperling, MD; Joaquin Sanchez-Sotelo, MD, PhD (JBJS Open Access)
Abstract. » A thorough understanding of glenoid deformity is essential to anticipate intraoperative needs and manage bony deficiencies. Management strategies include eccentric reaming, alternate scapular line baseplate orientation, bone grafting, or metallic augmentation as either “off-the-shelf” or custom baseplates. Accurate implantation of the glenoid component in the presence of glenoid bone loss (GBL) may also benefit from shoulderspecific guides, navigation, or robotic assistance. » GBL can negatively affect outcomes due to compromised bony fixation, altered soft tissue tensioning, and component malposition, which can contribute to impingement, dislocation, aseptic loosening, polyethylene wear, and component failure. » In this article, we provide a comprehensive review of published literature regarding the management of GBL in primary RSA and provide additional insight on the effectiveness of current approaches to manage bony deficiency.